THU0170 A MULTICENTER STUDY ASSESSING THE EFFICACY AND SAFETY OF REPOSITORY CORTICOTROPIN INJECTION IN PATIENTS WITH RHEUMATOID ARTHRITIS: INTERIM DATA FROM THE OPEN-LABEL TREATMENT PERIOD. (June 2019) - Fleischmann, Roy; Furst, Dan; Liu, Jingyu; Zhu, Julie; Connolly-Strong, Erin; Brasington, Richard
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disorder associated with chronic inflammation and is treated with disease-modifying anti-rheumatic drugs (DMARDs) for active disease. Both American College of Rheumatology (ACR) and EULAR recommend that short-term administration of corticosteroids (CSs) may be beneficial for its anti–inflammatory effects. Repository corticotropin injection (RCI) is a complex mixture containing purified porcine pituitary adrenocorticotropic hormone (ACTH)-analogue and an agonist for all 5 melanocortin receptors (MCRs). Activation of MCRs by ACTH has been shown to have direct and indirect anti–inflammatory and immunomodulatory effects. RCI is approved in the United States as adjunctive therapy for short–term administration in RA. Objectives: To present interim data after 100% enrollment from the initial 12-week open-label phase of a multicenter, 2–part study evaluating the efficacy, safety, and appropriate duration of RCI therapy in patients with persistently active RA despite receiving 1 or 2 DMARDs and/or CSs. Methods: In the open–label period (Part 1, Weeks 0–12), all enrolled patients received RCI 1 mL (80 U SC) twice weekly for 12 weeks. Patients who achieved low disease activity (LDA; DAS28-ESR score <3.2) at Week 12 continued in the double–blind, randomized maintenance phase of the trial (Part 2) for an additional 12 weeks. The primary endpoint was the proportion of patients who achieved LDA at Week 12. Secondary endpoints included assessment of the safety and tolerability of RCI. Disease activity was also assessed by the proportion of patients who achieved ACR 20%, 50%, and 70% (ACR20, 50, 70) responses and patient reported outcomes at Week 12. Bone turnover markers were assessed as an exploratory endpoint. Results: 259 patients had enrolled, 235 had completed and 24 had discontinued the 12-week open-label period of the study; 88.9% were female and mean age was 51 years. RCI treatment resulted in 62.5% of patients achieving LDA at Week 12; results for this interim analysis are presented in the Table . Bone turnover markers were stable from baseline to Week 12, indicating no effect of RCI on bone metabolism. 98 (37.8%) patients reported adverse events (AEs) with 3 (1.2%) patients reporting serious AEs (ie, non–cardiac chest pain, pneumonia, and craniocerebral injury). The most common AEs were urinary tract infection (n=10), headache (n=9), and pharyngitis (n=7). Conclusion: In the 12-week open label period of this study, RCI appeared to be generally safe and effective in patients with persistently active RA who were nonresponsive to DMARDs and CSs. This was demonstrated by improvement in multiple measures of disease activity. Further results will be evaluated in Part 2 of the study. Acknowledgement: Editorial support was provided by MedLogix Communications, LLC, Itasca, Illinois, under the direction of the authors and was funded by Mallinckrodt ARD LLC. Disclosure of Interests: Roy Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Dan Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS Corbus, NIH, Novartis, Pfizer, Roche/Genentech, Consultant for: AbbVie, Actelion, Amgen, BMS, Cytori, Novartis, Pfizer, Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company), Jingyu Liu Shareholder of: Mallinckrodt ARC, LLC, Employee of: Mallinckrodt ARC, LLC, Julie Zhu Shareholder of: Mallinckrodt ARC, LLC, Employee of: Mallinckrodt ARC, LLC, Erin Connolly-Strong Shareholder of: Mallinckrodt ARC, LLC, Employee of: Mallinckrodt ARC, LLC, Richard Brasington: None declared